PEMBERDAYAAN PEREMPUAN MELALUI TEKNOLOGI QUILLING PAPER SEBAGAI USAHA ALTERNATIF BERBASIS LINGKUNGAN DI DESA MARUNGGI KOTA PARIAMAN - Olyy Norita Tetra; Bustanul Arifin; Marniati Salim; Admin Alif; Zulhadjri Zulhadjri (Warta Pengabdian Andalas)
Empowering women through the improvement of quilling paper handicraft skill with paper waste material in Desa Marunggi, Kota Pariaman which is the first winner of West Sumatera Dasawisma but this has not been the activity of used paper mill into handicraft product with high selling price. The activity begins with environmental sanitation and health waste disposal training, advanced waste paper treatment training with quilling paper technology with modification process that is expensive expensive quilling paper paper with waste paper. Simple processing and combined with paper waste around the high crafts, artistic and unique products, such as wall decoration, souvenir, multipurpose box, miniature, jar, bag, tissue box, doll and others. The training activities were attended by ± 40 participants attended by women in PKK and heads of dasawisma groups. This activity is more interesting because it is held handicraft with handicraft goods from hand made. Through this dedication activity, it is hoped that the cooperation of universities and society so that can increase women's resources through home industry, increase knowledge, skills and is an improvement program of women participation in development.